Evaluate the Association Between Vitamin D Deficiency and Acute Otitis Media in Children at Birat Medical College and Teaching Hospital - Koirala, Bipin; Kumar Shah, Rajeev (Birat Journal of Health Sciences, 2025)
Introduction: Acute Otitis Media is the inflammation of the middle ear usually precipitated by an acute upper respiratory tract infection as a result of Eustachian tube dysfunction. Recent studies showed that Vitamin D might play a strong immunomodulatory role in incidence as well as severity in bacterial and viral infection showing an association of Low Vitamin D with increased risk of AOM and its recurrence and role of vitamin D supplement to prevent it. Objectives: To compare the association of Vitamin D deficiency in patient with acute otitis media attending Birat Medical College Teaching Hospital. Methodology: This is a hospital based comparative cross sectional study done in children aged between 1-14 years presenting in Birat Medical College Teaching Hospital from July 1st 2024 to Jan 31st, 2025. Purposive sampling was done in 80 children aged 1-14, where 40 patients with AOM was kept in group 1 and 40 children other than acute otitis media, chronic suppurative otitis media or any other ear disease were kept in group 2 . Serum vitamin D levels of all was assessed. Children's with any other systemic illness and congenital anomalies were excluded from the study. Results: Both the groups were demographically similar in terms of age and sex distribution. The proportion of insufficient Vitamin D is significantly higher in group 1 (90%) vs. group 2 (17.5%). Also group 1 had significantly lower average vitamin D levels (18.2ng/ml) vs. control (32.6ng/ml) (p-value <0.001) Conclusion: This study shows that low level of Vitamin D is associated with increased risk of acute otitis media and its recurrence.